ANTIPLATELET ACTIVITY OF ORIGINAL CLOPIDOGREL AND ITS GENERIC: RESULTS OF RANDOMIZED COMPARATIVE CROSS-OVER STUDY - V. V. Yakusevich; A. S. Petrochenko; V. S. Simonov; N. Yu. Levshin; A. D. Deev (Klinicist, 2014)
Objective — to study therapeutic equivalence (efficacy, safety and tolerability) and hemorheological activity of original clopidogrel and its generic in patients of high cardiovascular risk. Materials and methods. 50 patients with stable angina pectoris were randomized into 2 groups of consecutive 2-week treatment by original (plavix) and generic (plagril) clopidogrel and vice versa. ADP-induced platelet aggregation was measured at baseline and after treatment by each of the drugs. Physical examination and adverse events were evaluated at visits. Results. After the first treatment period a significant decrease of platelet aggregation was determined in both groups. After switching to another drug the decrease continued but not significantly in both groups. There were registered no adverse events associated with antiplatelet therapy. Conclusion. Equal antiplatelet activity established for plavix and plagril demonstrates their therapeutic equivalence.